2023
DOI: 10.3389/fimmu.2022.1088886
|View full text |Cite
|
Sign up to set email alerts
|

The application basis of immuno-checkpoint inhibitors combined with chemotherapy in cancer treatment

Abstract: Immuno-checkpoint inhibitors (ICIs) bring a promising prospect for patients with cancers, which restrains the growth of tumor cells by enhancing anti-tumor activity. Nevertheless, not all patients benefit from the administration of ICIs monotherapy. The partial response or resistance to ICIs is mainly due to the complex and heterogenous tumor microenvironment (TME). The combined therapy is necessary for improving the efficacy of tumor treatment. Chemotherapy is reported not only to kill tumor cells directly, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 137 publications
0
2
0
Order By: Relevance
“…Several studies have shown that chemotherapy could induce antigen presentation and induce expression of immune checkpoints ( 23 ). In addition, chemotherapeutic agents-induced immunogenic cell death and their immune stimulation activity are considered the main mechanisms of combination therapy ( 24 ). Therefore, early initiation of immunotherapy may be beneficial in LANPC.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that chemotherapy could induce antigen presentation and induce expression of immune checkpoints ( 23 ). In addition, chemotherapeutic agents-induced immunogenic cell death and their immune stimulation activity are considered the main mechanisms of combination therapy ( 24 ). Therefore, early initiation of immunotherapy may be beneficial in LANPC.…”
Section: Discussionmentioning
confidence: 99%
“…Patient responses to PD-1/PD-L1 blockade are not identical, and patients can be classified as responders, non-responders, and those who develop resistance based on their responses to anti-PD-1/PD-L1 antibodies 39 . As stated above, although anti-PD-1/PD-L1 antibodies exhibit potent antitumor effects in some patients, most patients do not benefit from PD-1/PD-L1 therapy due to primary or acquired treatment resistance 35 , 40 .…”
Section: Clinical Applications Of Pd-l1mentioning
confidence: 99%